Selective Laser-induced Etching for novel 3D microphotonic devices - Beckmann, Lara; Bi, Toby; Thoms, Julian M.; Wenk, Max; Zhang, Shuangyou; Kratz, Martin; Del'Haye, Pascal (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2024)
In this work, we evaluate the advantages and limitations of the Selective Laser-induced Etching (SLE) process for the fabrication of novel three-dimensional microresonator structures. Microresonators are resonant optical structures with the ability to store light of a specific wavelength. They are used as non-linear optical components, in sensors or even in integrated photonic devices. These structures are characterized by the optical quality factor Q as a measure of the optical storage capabilities. Q is significantly influenced by a high-quality optical surface with low surface roughness. In addition to surface quality and small dimensions, from tens of microns to millimeters, high optical nonlinearity is a key requirement in these fields. The fabrication of 3D fused silica parts fulfilling these requirements is an ongoing challenge in the field of microfabrication in quantum technology. The SLE process is used to fabricate three-dimensional parts of transparent materials such as fused silica with a high degree of geometric freedom in a two-step process. In the first step, a model of the part is written into the material using ultrashort pulse (USP) laser radiation. In the second step, the laser-written shape is wet-chemically etched in aqueous KOH to expose the part. The fabrication of 2D disk microresonators with high Q-factors is evaluated by studying the surface roughness of the SLE process followed by polishing. The polished samples are characterized and Q-factors >107 are achieved. In addition, the extent to which dimensions and geometry differ between design and real SLE components is analyzed. The SLE process will thus be investigated as a possible process for the future fabrication of three-dimensional microresonators.
CRIS-Team Scopus Importer:2024-05-03
Keywords: 3D micromachining; fused silica; in-volume structuring; laser micromachining; microresonators; selective laser-induced etching; SLE; ultrashort pulsed